Pectoralis minor length index at 1 month postoperative can predict homolateral neuropathic pain 4 months after mastectomy with lymph node resection - Asall Kim; Chunghwi Yi; Myungki Ji; Ui-Jae Hwang; Jae-Young Lim; Yujin Myung; Eun Joo Choi; Hee-Chul Shin; Jaewon Beom (PLoS ONE, 2025)
The relationship between postoperative physical changes and the development of homolateral neuropathic pain (HLNP) following mastectomy and lymph node resection remains poorly understood. In this study, we aimed to investigate whether early postoperative physical and symptom-based assessments could predict HLNP occurrence at 4 months post-surgery. Fifty-seven breast cancer survivors were included, with HLNP defined as a painDETECT Questionnaire score ≥ 13 at 4 months. Independent variables included patient demographics, physical function metrics including pectoralis minor length index (PMI), and questionnaire-based evaluations at 1 month postoperatively. Multivariate logistic regression identified systemic therapy side effects (ST) (odds ratio [OR]: 1.056; 95% confidence interval [CI]: 1.015–1.098) and PMI (OR: 0.204; 95% CI: 0.043–0.977) as significant predictors of HLNP. Receiver operating characteristic curve analysis identified cutoff values of 23.81 for ST and 9.82 for PMI. Reconstruction type and adjuvant therapy influenced the correlation between PMI and the number of resected lymph nodes, unlike external rotation metrics. Early assessment of ST and PMI facilitates HLNP risk prediction following breast cancer surgery. Multimodal interventions, including targeted physical therapy, may mitigate HLNP risk, highlighting the importance of early postoperative care.